Propuesta para la disminución de contaminantes en las aguas residuales provenientes de las piscinas termales del instituto de turismo de Paipa (2020)
The Paipa Tourism Institute is an establishment in charge of municipal public recreation, it is located in Paipa-Boyacá. This entity has a natural inflow of thermo-mineral water that springs from the so-called Pozo Azul, which feeds three thermal pools, which after 3 days the pool is completely emptied into the Chicamocha River through an outlet pipe, these discharges do not comply with the standards required by the Corpoboyacá entity, due to its high content of sulfate and chloride ions. On the other hand, it is known that these thermo-mineral waters have high salinity content and in turn this effluent is born on the surface of the lands surrounding the river, going to it without any treatment, causing damage to the nearby crops of this water source. since the farming community uses this water for their irrigation and animals. For this reason, this project aims to develop a proposal for the reduction of pollutants in wastewater from the thermal pools of the Paipa tourism institute, through ion exchange with a resin that allows the reduction of parameters such as chlorides and sulfates, evaluating their properties, in such a way that the choice is correct and effective for the reduction of these ions.